H01 Optimization of older adults’ home spaces to enhance their physical activity level and minimize sedentary behaviour: A qualitative study - Meghani, Naureen Akber Ali; Hudson, Joanne; Stratton, Gareth; Mullin, Jane (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
There is a lack of studies focused explicitly on the impact of the home environment on older adults’ sedentary behaviour (SB) and physical activity (PA). The present study aims to investigate older adults’ perception of their home environment and its impact on their PA and SB. A qualitative exploratory research design was employed to conduct 33 in-depth interviews (IDIs) and five focus group (FGs; n=16) with older adults (mean age 71.7 ± 5.2 years). Using reflexive thematic analysis as an inductive coding approach, four themes were generated from the data set and were interpreted using the socio-ecological model (SEM): (I) Home layout and PA, (II) Space designation within the home, (III) Electronic equipment, furniture and material within the home space, (IV) Changing infrastructure within the home space. The findings highlight the significance of person-environment interaction at different layers of the SEM. Older adults have a significant influence on the physical environment of the home and how it is organized in terms of allocating space and equipment. However, utilization of space, and its intentional use (for active or sedentary behaviour) is also crucial, emphasizing individuals’ autonomy, freedom and control within the home environment. Moreover, both interpersonal and intrapersonal factors act as facilitators or barriers regarding necessary modifications within the home space to promote a conducive environment for PA. The current findings provide insight into the interaction of personal, social, community, and physical environment factors to these older adults’ PA and SB in their homes. Moreover, motivating older adults to develop more intention to have positive control over their environment is important. Further, promoting the notion of ‘think small for large effects’ within the home space will enable older adults to map out small-scale activities (such as avoiding screens in the bedroom or moving PA equipment to a convenient place) instead of making large-scale, less realistic infrastructure changes.